Offshore Wind Power—Seawater Electrolysis—Salt Cavern Hydrogen Storage Coupling System: Potential and Challenges - Xiaoyi Liu; Yashuai Huang; Xilin Shi; Weizheng Bai; Si Huang; Peng Li; Mingnan Xu; Yinping Li (Energies)
Offshore wind power construction has seen significant development due to the high density of offshore wind energy and the minimal terrain restrictions for offshore wind farms. However, integrating this energy into the grid remains a challenge. The scientific community is increasingly focusing on hydrogen as a means to enhance the integration of these fluctuating renewable energy sources. This paper reviews the research on renewable energy power generation, water electrolysis for hydrogen production, and large-scale hydrogen storage. By integrating the latest advancements, we propose a system that couples offshore wind power generation, seawater electrolysis (SWE) for hydrogen production, and salt cavern hydrogen storage. This coupling system aims to address practical issues such as the grid integration of offshore wind power and large-scale hydrogen storage. Regarding the application potential of this coupling system, this paper details the advantages of developing renewable energy and hydrogen energy in Jiangsu using this system. While there are still some challenges in the application of this system, it undeniably offers a new pathway for coastal cities to advance renewable energy development and sets a new direction for hydrogen energy progress.